2013
DOI: 10.1007/s10461-013-0644-4
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Motives Among HIV Primary Care Patients

Abstract: Heavy drinking among individuals with HIV is associated with poor medication adherence and other health problems. Understanding reasons for drinking (drinking motives) in this population is therefore important and could inform intervention. Using concepts of drinking motives from previous alcohol research, we assessed these motives and drinking in 254 HIV-positive primary care patients (78.0% male; 94.5% African American or Hispanic) prior to their participation in an alcohol intervention trial. Three motives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 51 publications
(58 reference statements)
5
37
1
Order By: Relevance
“…As reported previously (Elliott et al, in press), participants reported typically consuming a mean of 5.68 (s.d. = 3.49) drinks per occasion, with a maximum consumption of 11.29 drinks (s.d.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…As reported previously (Elliott et al, in press), participants reported typically consuming a mean of 5.68 (s.d. = 3.49) drinks per occasion, with a maximum consumption of 11.29 drinks (s.d.…”
Section: Resultssupporting
confidence: 67%
“…Data analyzed in the present report were collected via Audio Computer-Assisted Self-Interview (A-CASI) in English or Spanish (patients’ preference) at baseline assessment, after enrollment in the study but prior to intervention participation. As described elsewhere (Elliott et al, in press), participants were mostly male (78.0%), and African American (49.6%) or Hispanic (44.9%). Their average age was 45.7 years (s.d.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations